2020
DOI: 10.1007/s00127-020-01983-w
|View full text |Cite
|
Sign up to set email alerts
|

Depression and anxiety symptoms among returning workers during the COVID-19 period in East China

Abstract: Purpose To determine the prevalence of depression and anxiety and associated factors among returning workers with different epidemic experience in East China. Methods A cross-sectional study was conducted among 2435 employees from the enterprises located in Deqing (low-risk epidemic area) and Taizhou (high-risk epidemic area) of East China in March 2020. An online questionnaire covered information on sociodemographic and lifestyle factors as well as knowledge, attitude, behavior and experience about COVID-19. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…The respondents of seven studies came from Hubei province (Cao H. et al, 2020 ; Fu et al, 2020 ; Huo et al, 2020 ; Luo F. et al, 2020 ; Yang T. et al, 2020 ; Yu et al, 2020 ; Zhou and Liu, 2020 ); the respondents of the thirteen studies came from provinces and cities other than Hubei province (Cao H. et al, 2020 ; Deng and Lei, 2020 ; Fu et al, 2020 ; Guo L. et al, 2020 ; Huo et al, 2020 ; Lin G. et al, 2020 ; Liu Z. et al, 2020 ; Sun Q. et al, 2020 ; Tan et al, 2020 ; Yang B. et al, 2020 ; Yang L. et al, 2020 ; Yang S. et al, 2020 ; Zhang J. et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…The respondents of seven studies came from Hubei province (Cao H. et al, 2020 ; Fu et al, 2020 ; Huo et al, 2020 ; Luo F. et al, 2020 ; Yang T. et al, 2020 ; Yu et al, 2020 ; Zhou and Liu, 2020 ); the respondents of the thirteen studies came from provinces and cities other than Hubei province (Cao H. et al, 2020 ; Deng and Lei, 2020 ; Fu et al, 2020 ; Guo L. et al, 2020 ; Huo et al, 2020 ; Lin G. et al, 2020 ; Liu Z. et al, 2020 ; Sun Q. et al, 2020 ; Tan et al, 2020 ; Yang B. et al, 2020 ; Yang L. et al, 2020 ; Yang S. et al, 2020 ; Zhang J. et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…The mechanism could be twofolded, as the Chinese study points out. Indeed, Yang et al found in their Chinese series that regular physical at-home workouts were significantly related to a decrease in the risk of developing depression and anxiety symptoms [ 26 ]. Regular physical exercise might reduce the risk of mental disorders that occur during the pandemic [ 27 ] and therefore decrease the emotional and psychological components of pain.…”
Section: Discussionmentioning
confidence: 99%
“…We carried out a cross-sectional study among the employees who had returned to work in Deqing and Taizhou, Zhejiang Province, China, from 5 March 2020 to 14 March 2020, the study design of which has been described previously [29,30]. At the beginning of our investigation, there were 3 confirmed cases in Deqing and 146 cases in Taizhou, and Deqing was classified as a low risk area and Taizhou as a high risk area for COVID-19 epidemic [31].…”
Section: Study Population and Designmentioning
confidence: 99%